BIOMONITORING PENCEMARAN UDARA MENGGUNAKAN BIOINDIKATOR LICHENES DI KOTA MADIUN - Anikhotul Ihrom; Ani Sulistyarsi (UNIVERSITAS PGRI MADIUN, 2015)
Bioindicators can be used to determine levels of air pollution of an area by analyzing the content of pollutants lead in bioindicators. Lichenes growing on the bark as bioindicators for measuring the concentration of lead in air pollutants resulting from motor vehicle emissions. The aim of research to determine differences in the levels of lead (Pb) using bioindicators Lichenes Madiun. Samples were taken by random sampling technique. Pb content measurement using Atomic Absorption Spectrophotometer (AAS). The results showed Pb levels in different areas of the City of Madiun there are significant differences. Traffic levels affect the levels of Pb .